Locus-specific DNA methylation in the placenta is associated with levels of pro-inflammatory proteins in cord blood and they are both independently affected by maternal smoking during pregnancy. Issue 10 (3rd October 2017) - van Otterdijk, Sanne D.; Binder, Alexandra M.; Michels, Karin B.
ABSTRACT: We investigated the impact of maternal smoking during pregnancy on placental DNA methylation and how this may mediate the association between maternal smoking and pro-inflammatory proteins in cord blood. The study population consisted of 27 individuals exposed to maternal smoking throughout pregnancy, 32 individuals exposed during a proportion of the pregnancy, and 61 unexposed individuals. Methylation of 11 regions within 6 genes in placenta tissue was assessed by pyrosequencing. Levels of 7 pro-inflammatory proteins in cord blood were assessed by electrochemiluminescence. Differential methylation was observed in the CYP1A1 promoter and AHRR gene body regions between women who smoked throughout pregnancy and non-smokers on the fetal-side of the placenta and in the GFI1 promoter between women who quit smoking while pregnant and non-smokers on the maternal-side of the placenta. Maternal smoking resulted in elevated levels of IL-8 protein in cord blood, which was not mediated by DNA methylation of our candidate regions at either the maternal or the fetal side of the placenta. Placental DNA methylation was associated with levels of inflammatory proteins in cord blood. Our observations suggest that maternal smoking during pregnancy affects both placental DNA methylation and the neonate's immune response.